STRATEGI PENGEMBANGAN DESA WISATA BLIMBINGSARI BERBASIS MASYARAKAT DI KABUPATEN JEMBRANA, BALI - Ni Ketut Merlyn Agustin Cahyaningsih; I Komang Gede Santhyasa (UNHI PRESS, 2021)
Blimbingsari Village is one of the tourist villages in Jembrana Regency. This village is an acculturation village of Balinese culture with Christians. This village has a rural natural atmosphere that is still very natural and very well organized, so it is considered to have the potential for developing a tourist village. The purpose of this study was to determine and formulate the potential that exists in Blimbingsari Village as a tourism village and how to develop its potential strategy. This study uses a qualitative approach with SWOT analysis. The data in this study were taken through interviews, observation and documentation. The results of this study indicate that there are 9 (nine) potentials to be developed as tourist villages consisting of; (1) The potential of the grojogan waterfall; (2) jungle tracking (jungle exploration); (3) Balinese cooking class (Balinese cooking class); (4) Village tour (Village tour); (5) Snorkelling (6) Bird watching tour; (7) Local conservation and farm tour (8) Cycling tour; and (9) Traditional painting and decorations. Based on the results of the SWOT analysis, it was found that Blimbingsari Village is currently in the development stage. The development strategy is directed at 3 things, namely; (1) Build a characteristic that is easy to remember by the wider community that distinguishes Blimbingsari Village from other villages that have almost the same potential; (2) Improvement of infrastructure, facilities and utilities as support in the Blimbingsari Tourism Village area; and (3) Increase public awareness, especially people of productive age about the importance of tourism or the benefits of tourism development for efforts to support regional economic development and improve community health.